2021
DOI: 10.17323/1814-9545-2021-1-52-73
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemic as a Challenge to the Development of University Networks in Russia: Differentiation or Collaboration?

Abstract: As an inevitable result of Russia's higher education policies of the past two decades, new university leaders in and outside of Moscow and St. Petersburg have emerged, and vertical differentiation has increased. Inequality of educational potential has a strong regional dimension, exerting a considerable delayed impact on regional socioeconomic development. Differences in universities' resources affected their ability to adapt their instructional, research, and administrative processes to change during the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, more progress is needed in creating operational response strategies through shared governance to respond to future episodes of health crises. Along these lines, it is recommended to broaden inter-institutional collaboration in the development of universities (Koksharov et al, 2021). In addition, structural changes are required to become more adept at meeting these challenges (Miller, 2021) using a holistic view to analyse the situation presented by all those involved.…”
Section: Discussionmentioning
confidence: 99%
“…However, more progress is needed in creating operational response strategies through shared governance to respond to future episodes of health crises. Along these lines, it is recommended to broaden inter-institutional collaboration in the development of universities (Koksharov et al, 2021). In addition, structural changes are required to become more adept at meeting these challenges (Miller, 2021) using a holistic view to analyse the situation presented by all those involved.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was found that the deterioration of the economic situation of families, fears associated with the spread of the disease, as well as the perception of electronic learning formats as less valuable, increases the cost and risks of moving to another city [25], which can lead to a decrease in the social mobility of applicants from small cities and remote territories, and, as a result, to a decrease in the demand of the population for higher education. Researchers suggest that educational and career trajectories will change in favor of early employment and preference for secondary vocational education organizations instead of universities [26]. However, the implementation of such a scenario is not obvious, since many states, in turn; take measures to increase the mobility of students, and studies confirming a real significant decrease in educational mobility are still insufficient [27].…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, there is a decrease in the level of post-school migration activity while maintaining a positive attitude towards higher education: more and more graduates are making a choice in favor of universities in their home region [18]. This can lead to a decrease in the social mobility of applicants from small towns and remote areas, a narrowing of the range of their educational opportunities [19]. Our study [7] of the peculiarities of admission to a regional university in the context of a pandemic has shown that a significant part of those admitted is young people living in cities of the regional level or district centers, whose families have an average income.…”
Section: Introductionmentioning
confidence: 99%